Israel's targeted killing policy: moral, ethical & operational dilemmas - Ganor, Boaz (Palgrave Macmillan, 2022)
Chapter 1. Overview - The use of targeted killing within Israel’s counter-terrorism policy over the years, its goals, characteristics and evolution in Israel -- Chapter 2. Potential Cost of Targeted Killing as a Counter-terrorism Strategy - Does Targeted Killing Trigger a Retaliatory "Boomerang Attack" -- Chapter 3.The death penalty – can a government act as a judge and an executioner? -- Chapter 4. The intelligence component of targeted killing – how does one prevent lethal mistakes? -- Chapter 5. The distinction principle of targeted killing – does a targeted killing of a terrorist means a deliberate hit on a combatant or a civilian? -- Chapter 6. The proportionality principle of targeted killing – Is a targeted killing really targeted? -- Chapter 7. The identity of the target – is there a justification to hit the political level of a terrorist organization or just its operational level? -- Chapter 8. Summary, Conclusions and Recommendations.